THE POSITION OF TNI-AD MEMBERS IN SOCIAL STRATIFICATION COMMUNITY IN KOTO LANANG DISTRICT, KERINCI REGENCY, JAMBI PROVINCE - Rahmawati, Tri Nurza (Walasuji : Jurnal Sejarah dan Budaya, 2020)
This research aims to explain and describe the position of TNI-AD in the social stratification community in Koto Lanang Village, Depati Tujuh District, Kerinci Regency. The theory used to analyze the findings in this research is the social stratification theory proposed by Max Weber. According to Weber, the basis of social stratification is characterized by several dimensions, namely the power dimension, the privilege dimension (special rights), and the pretense dimension. This research uses a qualitative approach with a descriptive type of research. The technique of selecting informants uses purposive sampling. The total number of informants is 30 people. Data are collected through interview, observation, and documentation methods. The result of this research reveals that the position of TNI-AD in the social stratification community in Koto Lanang Village is seen from several dimensions, including: (1) the power dimension, TNI-AD is the spearhead in every activity in Koto Lanang Village. (2) the privilege dimension (special rights), members of TNI-AD are included in a capable and sufficient society seen from an economic field; and (3) the prestige dimension, the people as members of TNI-AD are awarded by their society.